2015
DOI: 10.4049/jimmunol.1500849
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1 Is a T Cell–Intrinsic Inhibitor of the RORγt-Th17 Program

Abstract: An uncontrolled exaggerated Th17 response can drive the onset of autoimmune and inflammatory diseases. In this study, we show that, in T cells, Foxo1 is a negative regulator of the Th17 program. Using mixed bone marrow chimeras and Foxo1-deficient mice, we demonstrate that this control is effective in vivo, as well as in vitro during differentiation assays of naive T cells with specific inhibitor of Foxo1 or inhibitors of the PI3K/Akt pathway acting upstream of Foxo1. Consistently, expressing this transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 59 publications
3
93
0
Order By: Relevance
“…Furthermore, FoxO1 positively controls Foxp3 gene expression and maintains the proper functioning of Tregs to suppress autoimmunity (48,53). It has been shown that FoxO1 is a negative regulator of Th17 by inhibiting RORγt activity (54) and that inactivation of FoxO1 is essential for Tfh cell differentiation (55). Therefore, FoxO1 inactivation arising from genetic defects in both TET2 and RhoA could lead to an imbalance in effector T cells to induce inflammatory-like phenotypes such as those we observed in recipient mice after adoptive T cell transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FoxO1 positively controls Foxp3 gene expression and maintains the proper functioning of Tregs to suppress autoimmunity (48,53). It has been shown that FoxO1 is a negative regulator of Th17 by inhibiting RORγt activity (54) and that inactivation of FoxO1 is essential for Tfh cell differentiation (55). Therefore, FoxO1 inactivation arising from genetic defects in both TET2 and RhoA could lead to an imbalance in effector T cells to induce inflammatory-like phenotypes such as those we observed in recipient mice after adoptive T cell transfer.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 activity inhibits the formation of Th17 cells and suppresses the expression of IL-17A. FOXO1 inhibits IL-17A and IL-23 receptor expression in part by inhibiting the transcriptional activity of RORγt 64 by forming a complex with it. Therefore, FOXO1 acts a repressor of RORγt to inhibit Th17 differentiation.…”
Section: T Cellsmentioning
confidence: 99%
“…Therefore, FOXO1 acts a repressor of RORγt to inhibit Th17 differentiation. 64 Because of the inhibitory effect of FOXO1 on the formation of Th17 cells, antigen activation of the TCR is needed to reduce FOXO1 activity and permit Th17 cell differentiation. One of the key effector molecules in Th17 cells that inhibits FOXO1 activation is SGK1.…”
Section: T Cellsmentioning
confidence: 99%
“…Indeed, Foxo1 has critical functions in B cell development, homing, class-switch recombination and somatic hypermutation (Amin and Schlissel, 2008; Dengler et al, 2008). Foxo1 also regulates both naive and memory T cell survival and trafficking (Kerdiles et al, 2009; Kim et al, 2013; Ouyang et al, 2009; Ouyang et al, 2010), thymic regulatory T (tTreg) and peripheral regulatory T (pTreg) cell development and function (Kerdiles et al, 2010; Merkenschlager and von Boehmer, 2010; Ouyang et al, 2010; Ouyang et al, 2012), as well as T helper-1 (Th1), Th17 and T follicular helper (Tfh) cell differentiation (Kerdiles et al, 2010; Laine et al, 2015; Merkenschlager and von Boehmer, 2010; Oestreich et al, 2012; Ouyang et al, 2012; Stone et al, 2015). So far, no specific role for Foxo1 has been assigned in immune cells other than lymphocytes.…”
Section: Introductionmentioning
confidence: 99%